Incidence of SARS-COV-2 infection among swimming athletes: data from real life in Apulia (Italy), July 2020/ August 2021 - Stefanizzi, P.; Bianchi, F. P.; Ascatigno, L.; Pantaleo, N.; Martinelli, A.; Di Lorenzo, A.; Notarnicola, A.; Fischetti, F.; Tafuri, S. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. As other indoor sports facilities, swimming pools were closed in Italy from March to May 2020 and from October 2020 to July 2021 due to the outbreak of the COVID-19 pandemic; access to these facilities was restricted to athletes of national relevance. This decision was based on “precautionary principles” and without evidence of a high risk of SARS-COV-2 circulation among swimming pools’ attendants. The aim of this paper is to describe the pattern of SARS-COV-2 circulation among swimming athletes in Apulia (Southern Italy). Study design. The study aims to investigate the hypothesis that attending a pool increases the risk of SARSCOV-2 infection. The outcome measure is the incidence of SARS-COV-2 infection among swimming athletes compared with the general population. Methods. This is a retrospective cross-sectional study carried out in Apulia, Southern Italy. The study was performed through the analysis of both the database of the Italian Swimming Federation and the SARS-COV-2 infections in Apulia Region, from July 2020 to August 2021. Results. Among 2,939 federally licensed athletes, 221 had an history of SARS-COV-2 infection from July 2020 to August 2021, with an incidence of 75.2 /1,000. In the general Apulian population, during the same time span, the incidence of SARS-COV-2 infection was 67.3/1,000 and - considering the incidence rate ratio - there is no difference between the two populations (IRR=1.1; 95% CI=0.9-1.3; p>0.05). Conclusions. The incidence of SARS-COV-2 infection in Apulian swimmers showed no significant differences with the general population.